"Canaanites" or "Amorites"? A Study on Semitic toponyms of the second millenium BC in the Land of Canaan - Rahkonen, Pauli Ensio Juhani (Studia Orientalia Electronica, 2016)
The present study is based on the onomastics of the Land of Canaan during the second millennium BC. The results from onomastics are compared with the corresponding archaeological data and with parallel literary sources. The aim of the research has been to distinguish the different linguistic groups, especially the Canaanites and the Amorites, and to determine their principal areas of settlement. In accordance with the basic archaeological results, the toponyms show a dramatic change that took place in the Land of Canaan in the beginning of the Middle Bronze Age II (approximately 2000 BC). In the Land of Canaan there appeared toponymic types originating from the area of Phoenicia and spreading to the coastal area of modern Israel. Slightly later another kind of toponymic types appeared in the Galilee, the Judean Hill Country and in the Middle Zone of the Transjordan, the origin of which is to be found in Syro-Mesopotamia. It is remarkable that none of these particular types are found in the Hill Country of Ephraim.